PENGARUH EXPERIENTAL MARKETING DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN PADA ALFAMART CABANG SADIA I, KOTA BIMA - Shaiinnali, Ashabili; Ernawati, Sri; Hamidah, Nur Khusnul (STKIP MAJENANG, 2025)
Indonesian people's shopping trends tend to shift from traditional markets to modern retail for reasons of convenience, location affordability, and speed of service. This study aims to determine whether Store Atmosphere and Experiential Marketing have a significant effect on consumer purchasing decisions at Alfamart Sadia I branch either partially or simultaneously. The data collection method uses a questionnaire with a Likert scale. The population in the study were all consumers of Alfamart Sadia I branch with a sample size of 96 people. Data analysis techniques used multiple linear regression, t-test and f-test. The results of the study showed that Experiential Marketing had no significant effect on purchasing decisions, Store Atmosphere had a significant effect on purchasing decisions and Experiential marketing and store atmosphere had a significant effect on purchasing decisions.